2021
DOI: 10.3390/foods10061388
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Internal Packaging (Liners) on Moisture Dynamics and Physical and Physiological Quality of Pomegranate Fruit during Cold Storage

Abstract: Weight loss and decay are common physiological disorders during postharvest handling and storage of pomegranates. The study focused on relating the ability of plastic liners as internal packaging to modify both gaseous and moisture atmosphere around the fruit to moisture dynamics and physical and physiological quality of pomegranate fruit (cv. Wonderful) during storage. Fruit were packed with no-liner, non-perforated ‘Decco’, non-perforated ‘Zoe’, micro-perforated Xtend®, 2 mm macro-perforated high density pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…In fact, the slight differences found at the seventh day of storage could be related to the higher microbial metabolism of both the naturally present microbiota and inoculated pathogens. Similar results were reported when heat-shrinkable films were applied on pomegranate fruits [ 54 , 55 ] or in fruits differently packaged [ 56 ]. Moreover, the quality of pomegranate arils is strongly related to their red color, which mainly depends on the cultivar and on the ripeness state.…”
Section: Discussionsupporting
confidence: 83%
“…In fact, the slight differences found at the seventh day of storage could be related to the higher microbial metabolism of both the naturally present microbiota and inoculated pathogens. Similar results were reported when heat-shrinkable films were applied on pomegranate fruits [ 54 , 55 ] or in fruits differently packaged [ 56 ]. Moreover, the quality of pomegranate arils is strongly related to their red color, which mainly depends on the cultivar and on the ripeness state.…”
Section: Discussionsupporting
confidence: 83%
“…The results agree with Meighani et al [48], who showed that resin wax coatings on 'Malase Torshe Saveh' pomegranates before cold storage (4.5 • C) significantly reduced weight loss as compared to uncoated fruit. In addition, packaging of 'Wonderful' pomegranates with polyliners during cold storage has been reported to reduce weight loss [13,64]. Internal packaging creates a modified atmosphere that minimizes water migration from the fruit to the environment, often leading to desiccation [21,26].…”
Section: Total Phenolic Content and Free Radical Scavenging Activitymentioning
confidence: 99%
“…For instance, Mphahlele et al [ 14 ] reported that packing ‘Wonderful’ pomegranates in either ZOEpac polyliner bags or shrink wrapping reduced weight loss and maintained good visual appearance during 4 months of cold storage (7.5 ± 0.5 °C). Likewise, Lufu et al [ 15 ] showed that different MAP polyliners (micro-perforated Xtend ® , 2 mm macro-perforated high density polyethylene and 4 mm macro-perforated) minimized weight loss and the development of decay and shrivel in ‘Wonderful’ pomegranates stored at 5 °C for 84 d. Similar results were also reported when MAP technology was applied on several pomegranate cultivars including ‘Bhagwa’ [ 16 ], ‘Hicrannar’ [ 17 ] and ‘Primosole’ [ 18 ]. However, with the current trend towards sustainability of the environment and market, some technologies are categorized as unsafe, and customers prefer plastic-free packaging [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%